Land-use and land-cover affect inland fish catch in two rivers of Central Africa - Castello, L.; Anane-Taabeah Attu, G.; Aliebe, A.; Onana Ateba, N.O.; Jueya, S.; Carvalho, F.; Ickowitz, A.; Frimpong, E.A. (Elsevier, 2022)
Land-cover change can affect inland fisheries, which underpin food security of millions of people worldwide. Removal of forests from very large floodplains has been found to decrease fish catch via loss of feeding and nursery habitat for fish. However, it is unknown if similar effects occur in smaller rivers with limited floodplain areas. Little is also known about the mechanisms by which land-cover changes affect inland fish catch. Here, we assessed land-use and land-cover (LULC) effects on fish catch, diet, and condition at sites in two medium-sized rivers of Cameroon, in Central Africa. We found that LULC explained 30% of the variation in fish catch, with the catch of five species being positively, and of two species being negatively, related to floodplain forests. The niche breadth of fish diets was higher in the river surrounded by forests than in the river surrounded by agricultural land. However, contrary to expectations, condition of the fish, as indicated by occurrence of diseases or deformities, eroded fins, lesions or tumors, was not related to LULC. Our results support the notions that floodplain forests support fish populations in rivers with limited floodplain areas in ways similar to that of rivers with large floodplains, and that LULC affects fish populations via changes in fish diets and instream habitat features (i.e., riparian canopy closure, water clarity, substrate heterogeneity, and habitat volume). These effects imply that prevailing changes in LULC threaten the food and livelihood security services provided by inland fisheries, highlighting the importance of policies that maintain native vegetation along riverbanks and in floodplain areas.